2017
DOI: 10.1111/ejss.12426
|View full text |Cite
|
Sign up to set email alerts
|

Amendment with sugarcane pith improves the hydrophysical characteristics of saline‐sodic soil

Abstract: Summary The application of organic materials is an environmental practice in soil restoration, but the use of sugarcane pith, a by‐product of the paper industry, as an amendment in soil reclamation has not been tested so far. The objective of this study was to quantify the effects of the application of sugarcane pith on various hydrophysical properties of saline‐sodic soil. A 4‐month incubation pot trial under stagnant water and leaching conditions was carried out. Application of 5, 10 and 20 t ha−1 pith led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Ca 2+ , Mg 2+ , and K + ) in large amounts and in more available forms (Table 2), which transfer with the extract (Table 4). It could be due to the decrease ofswelling and dispersion of clays, which is considered a prerequisite for the formation of soil aggregates (Abd El-Halim and Lennartz, 2017;Chouhan et al, 2018 andDiacono &Montemurro, 2015). Electrolytes with Ca 2+ , in particular in the extract derived from CSP (Table 4), can attract soil particles and form very stable soil structural units by the coalescence of micro-aggregates (Hughes andGirdlestone, 2001); consequentlyaggregate stability increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ , Mg 2+ , and K + ) in large amounts and in more available forms (Table 2), which transfer with the extract (Table 4). It could be due to the decrease ofswelling and dispersion of clays, which is considered a prerequisite for the formation of soil aggregates (Abd El-Halim and Lennartz, 2017;Chouhan et al, 2018 andDiacono &Montemurro, 2015). Electrolytes with Ca 2+ , in particular in the extract derived from CSP (Table 4), can attract soil particles and form very stable soil structural units by the coalescence of micro-aggregates (Hughes andGirdlestone, 2001); consequentlyaggregate stability increases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the process of aggregation is supported by binding substances such as organic materials in general and organic acids in particular. Accordingly, various organic compounds and soil agglutinants, i.e., organic carbon (Table 4) and polysaccharides, are released in large amounts with the disintegration of FSP during the composting process, which transfer with the extract and facilitates aggregates formation and increases their stability (Annabiet al, 2011;Abd El-Halim and Lennartz, 2017;Bashir et al, 2016;Gülser et al, 2015;Sanjuán et al, 2001 andZhang et al, 2014). In addition, some organic matter sources are hydrophobic substances, which may also have increased the resistance of aggregates to slaking in water (Piccolo andMbagwu, 1999), the result is to increase the aggregate stability.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of aggregates can have large impacts on soil structure, thereby affecting the movement of water and plant nutrients (Franzluebbers, 2002;Bronick and Lal, 2005), microbial activities (Yazdanpanah et al, 2016) and root growth (Six et al, 2004). Other studies observed similar impacts on soil physical properties from the application of organic residues (Scotti, et al, 2015;Abd El-Halim and Lennartz, 2017). Wang et al (2017) and Yazdanpanah et al (2016) emphasized changes to structural properties from the application of many organic amendments to soils.…”
Section: Introductionmentioning
confidence: 95%
“…In this research, we observed that MWD and WSA were positively affected by the application of sugarcane pulp. This is attributed to the decomposition of sugarcane pulp during the wheat-growing season, especially during the first 2 months, and completely within 120 days (Cifuentes et al, 2013), leading to release (1) various binding substances such as organic materials in general and organic acids in particular, which increases MWD (Abd El-Halim and Lennartz, 2017;Wong et al, 2010 andZhong et al, 2017) and (2) various agglutinants such as polysaccharides, which increases WSA (Abd El-Halim & Lennartz, 2017;Ghosh et al, 2018;Khotabaei et al, 2013 andSix &Paustian, 2014). However, the effect of pulp on soil hydro-physical characteristics, particularly the MWD and WSA, depends on its decomposition rate, amounts of binding and agglutinants substances, and the amount applied (Trivedi et al, 2015).The increase in MWD and WSA can explain the observed decrease in BD and the simultaneous increase in TP (Abd El-Halim and Lennartz, 2017;Phullan et al, 2017 andThangasamy et al, 2017).…”
Section: Soil Hydro-physical Characteristicsmentioning
confidence: 99%